1988
DOI: 10.1002/mrd.1120190404
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizing potential of acrosome‐defective sperm following microsurgical injection into eggs

Abstract: Ejaculates from three infertile men were examined ultrastructurally and found to include a high number of amorphous acrosomeless spermatozoa. Two of the patient's spermatozoa exhibited the typical characteristics of round-head syndrome--spherical-shaped heads completely absent of acrosome and postacrosomal sheath. The semen of the third patient was found to contain a mixture of round-headed and irregularly shaped acrosomeless sperm and a small percentage of normal acrosome-intact sperm. Previous studies have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

1990
1990
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 13 publications
0
19
0
2
Order By: Relevance
“…Uehara and Yanagimachi (1976) have reported that sperm nuclei of hamsters developed into male pronuclei when they are injected into hamster eggs. Several investigators have also injected sperm into mammalian ova (Uehara and Yanagimachi, 1977;Witkowska, 1981;Komar, 1982;Markert, 1983;Lanzendorf et al, 1988). Keefer (1989) reported that rabbit spermatozoa and sperm nuclei can undergo both decondensation and pronuclear formation after microinjection into hamster and rabbit ova, and that ova fertilized by microinjection are capable of early cleavage and development.…”
Section: Discussionmentioning
confidence: 99%
“…Uehara and Yanagimachi (1976) have reported that sperm nuclei of hamsters developed into male pronuclei when they are injected into hamster eggs. Several investigators have also injected sperm into mammalian ova (Uehara and Yanagimachi, 1977;Witkowska, 1981;Komar, 1982;Markert, 1983;Lanzendorf et al, 1988). Keefer (1989) reported that rabbit spermatozoa and sperm nuclei can undergo both decondensation and pronuclear formation after microinjection into hamster and rabbit ova, and that ova fertilized by microinjection are capable of early cleavage and development.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemisch weisen diese Spermien keine oder eine stark verringerte Aktivität der akrosomalen Serin-Protease Akrosin und des Cytoskeletproteins Calicin auf (Flörke-Gerloff et al 1984;Longo et al 1987;Lalonde et al 1988;Escalier 1990;Courtot 1991). Die Akrosomen-losen Spermatozoen können zwar nicht an die Zona pellucida binden und diese penetrieren, sie sind aber zur Dekondensation des chromosomalen Materials fähig, wie durch Injektionsexperimente in Hamster-Oozyten nachgewiesen werden konnte (Weissenberg et al 1982, Lanzendorf et al 1988). Problematisch hat sich die Globozoospermie bei der Anwendung von ICSI herausgestellt, da sich etwa bei der Hälfte der Paare die Eizellen nach Injektion von rundköpfigen Spermatozoen nicht entwickeln.…”
Section: Humane Syndrome Mit Männlicher Infertilitätunclassified
“…Lanzendorf et al [27] recently presented data that for those with absent or markedly deficient acrosome reaction, there is still some potential chance for fertilization to occur following microsurgical injection of ova with acrosome-deficient sperm. In three separate males with absent acrosome reactions it was demonstrated that sperm were capable of decondensation and pronuclear formation.…”
Section: Acrosome Reactionmentioning
confidence: 99%